Efficient Method of an Optimal Construction Company Supplier Selection Supported by Software - Jozef Gašparík; Peter Bažík; Vít Motyčka (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
An optimal selection of production and services company suppliers is one of the most important processes of the top management. According to ISO 9001:2015 developed for Quality Management System the type and range of control to be applied to the outsourced process can be influenced by many factors. There are several factors and criteria for the efficient selection of company suppliers. Our paper analyses the following factors: quality management level of suppliers, offered price of the construction process or product and time of construction process realisation. Using the multi-criterion optimising method and scientific synthesis a method of the efficient selection of suppliers for external processes is proposed. In addition, we present our original software, which allows for an optimal selection of suppliers over a short course of time. This efficient method and software is implemented and verified on a real example from a real construction practice. Application of this method and software will increase the efficiency of the company supplier selection from the point of the key criteria of optimising: quality, time, cost and others. This efficient method and software can be applied in any company, which cooperates with one or more suppliers in a production and service process.
Keywords: Z31; L24; 330; construction; company; quality; supplier; optimization; criteria; software